Make Winning a Habit: 20 Best Practices of the World's Greatest Sales Forces - Page Rick (U.S.A : MC Graw Hill, 2006)
A master of the complex sale and a bestselling author, Rick Page is also one of the most experienced sales consultants and trainers in the world. Make Winning A Habit defines the gap between what companies know to do and how they consistently perform.
Page clearly identifies five “Ts” of transformation: Talent, Technique, Teamwork, Technology and Trust. These five elements, when fully developed and integrated into the sales and marketing organization, begin to create the habit of winning over customers in every industry. Stories of successes-and failures-from members of prominent companies help you apply the five “Ts” to your company's culture, and point the way to more effective plans for motivating employees, building and coaching winning teams, and improving hiring processes.
Keywords: Sales managment; Selling; Customer relations; Sale personel--training of